2020
DOI: 10.1525/collabra.281
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Mental Imagery Instructions and Personality Characteristics on Reading Experiences

Abstract: It is well established that readers form mental images when reading a narrative. However, the consequences of mental imagery (i.e. the influence of mental imagery on the way people experience stories) are still unclear. Here we manipulated the amount of mental imagery that participants engaged in while reading short literary stories in two experiments. Participants received pre-reading instructions aimed at encouraging or discouraging mental imagery. After reading, participants answered questions about their r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 55 publications
(100 reference statements)
1
8
0
Order By: Relevance
“…Implicit instructions to use imagination when reading a story and individual's vividness of imagery predict the ability to become absorbed in a story (Mak, de Vries, & Willems, 2020). Yet, it is unclear to what extent this increased absorption is due to increased mental simulation.…”
Section: Individual Differences In Imagery: From Aphantasia To Hyperp...mentioning
confidence: 99%
“…Implicit instructions to use imagination when reading a story and individual's vividness of imagery predict the ability to become absorbed in a story (Mak, de Vries, & Willems, 2020). Yet, it is unclear to what extent this increased absorption is due to increased mental simulation.…”
Section: Individual Differences In Imagery: From Aphantasia To Hyperp...mentioning
confidence: 99%
“…This seems particularly desirable in view of similar recent experiments which observed a stronger impact of rather stable reader traits on experience and processing of narratives than state-level variables, i.e., narrative voice of reading stimuli and mental imagery instructions during reading, respectively (Hartung et al, 2017a;Mak et al, 2020). The available evidence suggests that the effects of reading short narratives is, to a relatively large degree, determined by pre-existing reader traits, and less so, if at all, by state variables including textual variations.…”
Section: Discussionmentioning
confidence: 98%
“…The first study (Mak & Willems, 2019 ) investigated different kinds of mental simulation during narrative reading, the second study (Eekhof et al, 2018 ) tested the influence of verb tense on mental simulation during literary reading, and the third study (Mak et al, 2020 ) investigated the influence of prereading instructions on reported mental imagery and other subjective reading experiences.…”
Section: Methodsmentioning
confidence: 99%
“…that we adapted from Knoop and colleagues ( 2016 ). Studies 2 (Eekhof et al, 2018 ) and 3 (Mak et al, 2020 ) both omitted one adjective from the list (Study 2: Special ; Study 3: Entertaining ), resulting in 11 adjectives that were included in the lists in all three studies. The resulting 11 adjectives that were included in the analysis can be found in Table 3 .…”
Section: Methodsmentioning
confidence: 99%